A Fair Share for Women : Cambodia Gender Assessment - UNIFEM; World Bank; ADB; UNDP; DFID (Phnom Penh, 2013)
The Government of Cambodia, as well as donors, is increasingly recognizing the importance of addressing gender issues in poverty reduction strategies and development goals in order to promote sustainable development for women and for the whole population. Gender disparities in access to and control of a wide range of human, economic and social resources and opportunities must be eliminated if Cambodia is to reduce poverty. The need to engender the process and outcomes of development strategy formulation and the identification of development goals, targets and indicators requires a comprehensive gender mainstreaming strategy. The State plays a central role in the promotion of gender equality. Thus, a significant commitment from government agencies across sectors and at all levels is needed to examine and revise agency policies and practices to address gender inequality. This report assesses the gender "terrain" in Cambodia. The assessment is based on a review of existing information from government, donor and non-governmental organization (NGO) sources and also from extensive consultations with various stakeholders. Limited original analysis was carried out for this assessment and there are several areas, such as changing gender relations and issues affecting men, which have not been covered due to lack of information or time.